Life-Based Learning Dengan Menggunakan Pendekatan Living Value Instruction dalam Tradisi Akademik Pesantren - Agus Fawait (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Pesantren as understated institutions are often stigmatized skewed as camouflage life, because it is always struggling with the issue of the afterlife. Then boarding reviled as the center of the life of a fatalist, because of its role of producing a pattern of life that leave the material world. Even more 'rough' is when boarding has been named as the center of radicalism. This certainly is the stigma of one of the boarding school, because essentially boarding an ideal educational institution that delivered between mental spiritual with intellectual learning models that Life Based Learning with living menggukan value approach. This paper examines what the position actually send in pursuit of pesantren in life values in students, from the aspect of independency, simplicity, teamwork and helping each student turns delivering the boarding school to become independent in treading living beings in society. Learning from real life and experience directly when in a composed boarding school, boarding school students were able to deliver into beings who are steadfast in the establishment, firmly in endurance in running life.Keywords: Life-Based Learning, Living Value, Academic Tradition, Pesantren